2018
DOI: 10.1103/physrevd.97.124013
|View full text |Cite
|
Sign up to set email alerts
|

Noether and Abbott-Deser-Tekin conserved quantities in scalar-tensor theory of gravity both in Jordan and Einstein frames

Abstract: We revisit the thermodynamic aspects of the scalar-tensor theory of gravity in the Jordan and in the Einstein frame. Examining the missing links of this theory carefully, we establish the thermodynamic descriptions from the conserved currents and potentials by following both the Noether and the Abbott-Deser-Tekin (ADT) formalism. With the help of conserved Noether current and potential, we define the thermodynamic quantities, which we show to be conformally invariant. Moreover, the defined quantities are shown… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 80 publications
1
20
0
Order By: Relevance
“…Finally, one has now to use Einstein field equations to introduceT ab inside Eq. (17). As already mentioned above, Einstein equations are not invariant under conformal transformations.…”
Section: B First Law In Einstein Framementioning
confidence: 89%
See 2 more Smart Citations
“…Finally, one has now to use Einstein field equations to introduceT ab inside Eq. (17). As already mentioned above, Einstein equations are not invariant under conformal transformations.…”
Section: B First Law In Einstein Framementioning
confidence: 89%
“…Therefore, only the second and last terms on the right-hand side will be kept in Eq. (17). Finally, one has now to use Einstein field equations to introduceT ab inside Eq.…”
Section: B First Law In Einstein Framementioning
confidence: 99%
See 1 more Smart Citation
“…There is another elegant approach developed independently in General theory of Relativity (GR) for the formulation of the thermodynamic description from the conserved charges, which is popularly known as the Abbott-Deser-Tekin (abbreviated as ADT) approach [4][5][6][7]11]. This formulation works well not only for asymptotically flat black hole spacetimes in GR, but also for the anti-deSitter (AdS) spacetimes in GR [4] as well as higher order gravity theories [5][6][7] (For the thermodynamic description using the ADT approach, also see the recent works [12][13][14][15][16][17][18][19][20][21][22]). Recently, the ADT approach has been extended successfully by us in the scalar-tensor theory as well, where we have also shown that the two approaches (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, in some sense, the offshell generalized ADT formalism could also be viewed as the cousin of both the BBC and phase space approaches. Till now, there have existed a series of developments and applications of the off-shell ADT formulation in a range of gravity theories regardless of the asymptotic behavior of the spacetime metrics [32,33,34,35,36,37,38,39,40,41,42,43,44,45,46].…”
Section: Introductionmentioning
confidence: 99%